The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5194/amt-11-4373-2018
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in 317–780 nm radiance reflected from the sunlit Earth during the eclipse of 21 August 2017

Abstract: Abstract. Ten wavelength channels of calibrated radiance image data from the sunlit Earth are obtained every 65 min during Northern Hemisphere summer from the EPIC (Earth Polychromatic Imaging Camera) instrument on the DSCOVR (Deep Space Climate Observatory) satellite located near the Earth–Sun Lagrange 1 point (L1), about 1.5 million km from the Earth. The L1 location permitted seven observations of the Moon's shadow on the Earth for about 3 h during the 21 August 2017 eclipse. Two of the observations were ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The wavelength region from near UV at 388 nm to NIR at 780 nm bears about half of the total solar irradiance of 1,361 W/m 2 (Kopp & Lean, ). The polynomial interpolation of the response of reflectance at five wavelengths is used to estimate the response of spectral reflectance for computing spectral integrated irradiance response, similar to the method by Herman, Wen, et al () for estimating the impact of the solar eclipse on reflected solar irradiance. The percent response of the reflected solar radiance between 388 and 780 nm can be obtained as spectral solar irradiance weighted response as italicRSP=388780Rs()λF0()λnormaldλ388780F0()λnormaldλ×100 where R s ( λ ) is the percent response for wavelength λ estimated from polynomial interpolation from the response at five EPIC wavelengths and F 0 ( λ ) is the TOA spectral solar irradiance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wavelength region from near UV at 388 nm to NIR at 780 nm bears about half of the total solar irradiance of 1,361 W/m 2 (Kopp & Lean, ). The polynomial interpolation of the response of reflectance at five wavelengths is used to estimate the response of spectral reflectance for computing spectral integrated irradiance response, similar to the method by Herman, Wen, et al () for estimating the impact of the solar eclipse on reflected solar irradiance. The percent response of the reflected solar radiance between 388 and 780 nm can be obtained as spectral solar irradiance weighted response as italicRSP=388780Rs()λF0()λnormaldλ388780F0()λnormaldλ×100 where R s ( λ ) is the percent response for wavelength λ estimated from polynomial interpolation from the response at five EPIC wavelengths and F 0 ( λ ) is the TOA spectral solar irradiance.…”
Section: Resultsmentioning
confidence: 99%
“…The near UV at 340 and 388 nm and the visible and the NIR channels allow us to derive aerosol and cloud properties in particular, while the oxygen A and B bands enable us to derive the altitude of cloud and dust plumes (e.g., Davis et al, ; Xu et al, ; Yang et al, ). EPIC images were used to quantify the reduction of reflected sunlight during the 2017 solar eclipse in North America (Herman, Wen, et al, ). Marshak et al () found terrestrial glint over land seen from DSCOVR/EPIC and interpreted the observations of bright flashes as specular reflections off nearly horizontal‐oriented tiny ice platelets floating in the air.…”
Section: Introductionmentioning
confidence: 99%
“…That process requires matching the EPIC and LEO imagers in time and space with the same viewing and illumination conditions. To calibrate the UV channels, Herman et al (2018a) used reflectances measured by the Ozone Mapping and Profiler Suite (OMPS) on the Suomi National Polar-orbiting Partnership (S-NPP) satellite. The VIS/NIR channels outside of the oxygen absorbing bands have been calibrated using reflectances from the MODerate-resolution Imaging Spectroradiometer (MODIS) on the Terra and Aqua platforms and from the S-NPP Visible Infrared Imaging Suite (VIIRS) (Haney et al, 2016;Geogdzhayev and Marshak, 2018;Doelling et al, 2019a;Geogdzhayev et al, 2021).…”
Section: Remote Sensing Instruments On Dscovrmentioning
confidence: 99%
“…3d, e). The Suomi National Polar-orbiting Partnership (Suomi NPP) satellite (Hillger et al, 2013) overpassed the Columbia site at 18:30 UTC when the site was in partial eclipse. The average cloud-top height from Visible Infrared Imaging Radiometer Suite (VIIRS) thermal infrared retrieval around the Columbia site was about 230 mb.…”
Section: Atmospheric and Surface Propertiesmentioning
confidence: 99%